2017
DOI: 10.3390/genes8100239
|View full text |Cite
|
Sign up to set email alerts
|

Houttuynia cordata Facilitates Metformin on Ameliorating Insulin Resistance Associated with Gut Microbiota Alteration in OLETF Rats

Abstract: Metformin and Houttuynia cordata are representative anti-diabetic therapeutics in western and oriental medicine, respectively. The current study examined the synergistic anti-diabetic effect of Houttuynia cordata extraction (HCE) and metformin combination in Otsuka Long–Evans Tokushima Fatty (OLETF) rats. Fecal microbiota were analyzed by denaturing gradient gel electrophoresis (DGGE) and real-time PCR. Combining HCE + metformin resulted in significantly ameliorated glucose tolerance (oral glucose tolerance te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 67 publications
2
27
1
1
Order By: Relevance
“…In the present study, treatment of HFD-fed animals with metformin and HCE in combination led to a greater improvement in OGTT parameters than higher doses of metformin or HCE alone, suggesting the synergistic beneficial impact of these two therapeutic agents on glucose tolerance as well as insulin sensitivity/resistance. Furthermore, in a previous study, using relevant in vitro and in vivo models, we showed that treatment with metformin + HCE was more beneficial than metformin alone in the improvement of glucose uptake, insulin secretion, glucose metabolism and insulin sensitivity ( 23 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the present study, treatment of HFD-fed animals with metformin and HCE in combination led to a greater improvement in OGTT parameters than higher doses of metformin or HCE alone, suggesting the synergistic beneficial impact of these two therapeutic agents on glucose tolerance as well as insulin sensitivity/resistance. Furthermore, in a previous study, using relevant in vitro and in vivo models, we showed that treatment with metformin + HCE was more beneficial than metformin alone in the improvement of glucose uptake, insulin secretion, glucose metabolism and insulin sensitivity ( 23 ).…”
Section: Discussionmentioning
confidence: 93%
“…After grinding, powder of Houttuynia cordata was extracted by 5 L ethanol recycling reflux for 4 h. The extract was then filtered and vacuum lyophilized at −70°C, which gave a 5.82% yield. The HCE contained 3.63% quercitrin, 0.45% quercetin and 0.99% of isoquercitrin ( 23 ). Metformin was purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To elucidate the mechanism underlying SH treatment during post-infarct remodeling, the AMPK and NF-κB signal pathways were further investigated. It has been reported that AMPK was one of the downstream signal pathways of Cordata Houttuynia treatment under diseased situations ( Kang and Koppula, 2014b ; Wang J.H. et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AMPK has been confirmed exerting pleiotropic functions against inflammatory response and tissue fibrosis and owning beneficial properties in a series of diseases ( Peairs et al, 2009 ; Chiang et al, 2017 ; Kim et al, 2017 ). Intriguingly, recent studies have found activation of AMPK could be elicited or enhanced by H. cordata treatment in diseased situations ( Peairs et al, 2009 ; Xu et al, 2015 ; Wang J.H. et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%